Specyfika etyk kobiecych w ujęciu Carol Gilligan - HORDECKI, Bartosz (Przegląd Politologiczny, 2018)
The paper discusses the ethical views of Carol Gilligan that emerged to dispute the theory of six stages of moral development developed by Lawrence Kohlberg. In his opinion, women tend to reach the higher stages of his scale less frequently than men do. According to C. Gilligan this does not evidence the moral supremacy of men over women, but the faulty de- sign of the research tool. In her opinion, the Kohlbergian conception was based on an ethics of justice that took into account an exclusively male point of view. Women, whose voice is not heard in the public sphere, adopt a different type of ethics, namely the ethics of caring. C. Gilligan believes that it is necessary to promote this specific type of female ethics in order to overcome male dominance which is harmful both for women and men. Introducing a fe- male ethics will make it possible to refute the ‘double lie’ underlying patriarchal civilization. The lie involves (1) the assumption that male ethics are universal; and (2) female concealment of their own models of moral reasoning.